A review of design characteristics of cognitive behavioral therapy-informed behavioral intervention technologies for youth with depression and anxiety. (November 2016) - Stiles-Shields, Colleen; Ho, Joyce; Mohr, David C
Objective: Cognitive behavioral therapy (CBT) has the strongest evidence base for the prevention and treatment of depression and anxiety in youth. Behavioral intervention technologies (BITs) provide an opportunity to overcome access barriers to traditional delivery of CBT. The present review evaluates the design characteristics of CBT-informed BITs for depression and anxiety designed for and tested with youth. Methods: A state-of-the-art review of three library databases (PubMed, Scopus, and Web of Science) was conducted to identify papers that evaluated the use of CBT-informed BITs for the prevention and/or treatment of depression and anxiety among youth. Narrative results of design characteristics were organized using the BIT model, which provides a framework for design and evaluation. Results: 219 unique results were retrieved through the search. After review, 14 papers (4 prevention and 10 treatment) met the selection criteria. A broad diversity occurred in reporting the design and methodology of CBT delivered to youth through BITs. Psychoeducation was overwhelmingly utilized as the primary change strategy throughout the interventions, with a heavy use of content delivery elements and linear workflows. The reporting of sample characteristics was minimal and varied. Conclusions: Providing psychoeducation via content delivery was the most utilized BIT change strategy in the interventions, likely limiting the use of multiple BIT elements or flexible workflows. While characterizations could be inferred from the current reports, the high level of variability in reporting is problematic. Generalizability becomes increasingly more difficult to carry out effectively without clear descriptions of the design for evaluated BITs.